The Prevalence of Optic Neuropathy in Alcoholic Patients—A Pilot Study. (24th June 2014) - Donnadieu‐Rigole, Hélène; Daien, Vincent; Blanc, Dominique; Michau, Stéphanie; Villain, Max; Nalpas, Bertrand; Perney, Pascal
<x xml:space="preserve">Abstract</x> Background Alcohol has particularly toxic effects on the central and peripheral nervous systems. Optic neuropathy (ON) is one of these neurological complications. Its diagnosis has not been codified, and its prevalence is poorly known. The aim of this pilot study was to assess the prevalence of ON and identify risk factors in a cohort of patients hospitalized for alcohol withdrawal. Methods This was a single‐center prospective study. A complete standardized eye examination was performed during the patient's alcohol withdrawal; The data collected included: sociodemographic status; the number of withdrawals; the type and amount of alcohol drunk, tobacco, and illicit drug consumption; and ophthalmological results. Results One hundred patients were included prospectively from January 2010 to June 2011 (67 men and 33 women) with a mean age of 47 ± 12 and 46 ± 10 years, respectively. The average alcohol consumption was higher for men than women: 207 ± 122 vs. 146 ± 92 g/d, p = 0.013. The most frequent definition of ON in the literature is a decrease in visual acuity associated with impaired color vision. Thirteen percent of men and 3% of women met these criteria. But monocular ON was observed in 22% of men and 18% women, and partial damage was demonstrated in 27% of men and 7% of women. Conclusions ON is a relatively rare complication of chronic alcohol consumption, but the high prevalence of incomplete forms should prompt screening and early treatment.